pengujian karakteristik alat perajang porang - Jufri Efendi Solin; Mikhratunnisa (The Journal of Teknologi Pangan, 2022)
Porang (Amorphophallus muelleri) is a type of bulbous plant that grows naturally in almost all forests in Indonesia. Porang usually grows in areas with secondary vegetation, gardens, teak forests, and village forest edges. Porang plants can generally grow on all types of soil. Along with the development of increasingly sophisticated technology and the need for machines that can increase the production of agricultural products and snack food craftsmen, especially processed products from tubers. Therefore, we need a tool that facilitates the processing of the snack food industry with optimal results and relatively cheap prices. Characteristics of measuring instruments is a comprehensive measurement (preparation, implementation and analysis) that can be relied on for its success. One will not be able to design measurements correctly without knowing the meaning of the characteristics of the measuring instrument. The purpose of this study was to determine the characteristics of the porang chopper using tools. The result of the process of testing the cutting capacity of 818.836 kg/hour. Then the results of the average thickness is 5.6854 mm. The results of the percentage of damaged materials as much as 0.0744%. And the result of the percentage of materials left in the tool is 0.026%.